2021
DOI: 10.3390/f12050543
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Natural Volatile Organic Compounds Emitted by Bamboo Groves in Urban Forests

Abstract: Due to the COVID-19 outbreak, people in countries around the world including the United Kingdom, Denmark, Canada, and South Korea are seeking physiological and psychological healing by visiting forests as stay-at-home orders continue. NVOCs (natural volatile organic compounds), a major healing factor of forests, have several positive effects on human health. This study specifically researched the NVOC characteristics of bamboo groves. This study revealed that α-pinene, 3-carene, and camphene were observed to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…On the other hand, studies that measured the terpene concentration in ambient air showed diverse diurnal patterns. Several studies that measured BVOC and terpene concentration in the ambient air showed diurnal patterns that were similar to ours [ 29 , 30 ], while other studies showed different diurnal patterns of high BVOC and terpene concentrations in the morning and before sunset and lower concentrations in the middle of the day [ 25 , 31 , 32 , 64 ]. Comparing the two types of results from other studies, the difference in diurnal terpene emission patterns between the two types of measurement scheme arises from the mixing effect related to wind speed and rapid chemical reactions with other materials in the air (e.g., ozone formation) [ 27 , 30 , 32 , 63 , 65 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, studies that measured the terpene concentration in ambient air showed diverse diurnal patterns. Several studies that measured BVOC and terpene concentration in the ambient air showed diurnal patterns that were similar to ours [ 29 , 30 ], while other studies showed different diurnal patterns of high BVOC and terpene concentrations in the morning and before sunset and lower concentrations in the middle of the day [ 25 , 31 , 32 , 64 ]. Comparing the two types of results from other studies, the difference in diurnal terpene emission patterns between the two types of measurement scheme arises from the mixing effect related to wind speed and rapid chemical reactions with other materials in the air (e.g., ozone formation) [ 27 , 30 , 32 , 63 , 65 ].…”
Section: Discussionsupporting
confidence: 81%
“…Our method is based on the rate of emission of terpenes directly from trees, and the result differs from the concentration-based methods sampling ambient air. The therapeutic effect of forest bathing and inhaling terpenes is directly related to the terpene concentration in the ambient air, which is not only associated with the terpene emission rate from trees but also closely related to microclimatic factors, such as humidity and wind speed and direction [ 25 , 31 , 32 , 63 , 64 ]. Therefore, there is a need for a deeper understanding and consideration of the microclimate in order to estimate the spatiotemporal variation of terpenes directly affecting humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the health-promoting effects of the phytoncides emitted by plants are acknowledged, the demand for research on phytoncides is increasing. Several prior studies have been conducted to detect the phytoncide concentration emitted by forests and to investigate the effect of forest healing [4][5][6][24][25][26]. However, concerning forests, due to the nature of the outdoor environment, changes in phytoncide emissions are affected by various microclimate environments and abiotic factors [20,24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of forests and the species that make up the forests, it is known that the amount and type of monoterpene emitted differs. Generally, higher concentrations of monoterpene are produced in coniferous forests than in broadleaf forests [38][39][40][41].…”
Section: Introduction 1research Background and Rationalementioning
confidence: 99%